2005
DOI: 10.1128/aem.71.11.7562-7566.2005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Listeria spp. in Effluents of French Urban Wastewater Treatment Plants

Abstract: Listeria spp. were found in most treated waters (84.4%) and raw sludge (89.2%) of six French urban wastewater treatment plants and one composting facility, examined monthly over a 1-year period. Most strains belonged to Listeria monocytogenes, serotypes 4b/4e being predominant. Sludge composting and liming reduced or prevented Listeria contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
52
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 16 publications
8
52
0
2
Order By: Relevance
“…Since many different contamination routes for this ubiquitous bacterium have been reported (19,27,34), the development of rapid and accurate typing methods is of particular importance. A substantial number of sensitive, discriminatory, and reproducible typing technologies have therefore been developed (20).…”
mentioning
confidence: 99%
“…Since many different contamination routes for this ubiquitous bacterium have been reported (19,27,34), the development of rapid and accurate typing methods is of particular importance. A substantial number of sensitive, discriminatory, and reproducible typing technologies have therefore been developed (20).…”
mentioning
confidence: 99%
“…Although rare, the disease is reported (Lyautey et al, 2007) to have a very high mortality rate (20-50%), thus making it of serious public health concern. Despite the general consensus that food is the primary route of transmission of this disease, wastewater has long been reported to be a potential reservoir for Listeria species and possible source of transmission (Paillard et al, 2005;Arslan and Ozdemir, 2008). Watkins and Sleath (1981) reported the prevalence of Listeria species in sewage at numbers far higher than those of Salmonella species.…”
Section: Listeria Monocytogenes In the Human And Animal Environmentmentioning
confidence: 99%
“…Watkins and Sleath (1981) reported the prevalence of Listeria species in sewage at numbers far higher than those of Salmonella species. And recent studies suggest that Listeria species readily survive conventional wastewater treatment processes even after tertiary treatment (Paillard et al, 2005).…”
Section: Listeria Monocytogenes In the Human And Animal Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…in a longitudinal study in sediment and water plant samples have not yet been reported. Other studies focus on L. monocytogenes in waste water and sludge [68], fresh surface water and untreated sewage [69], sewage, sewage sludge and river water specimen [70]. These studies report n.s., not specified.…”
Section: Cell Counts Of Listeria Speciesmentioning
confidence: 99%